1992
DOI: 10.1180/minmag.1992.056.384.02
|View full text |Cite
|
Sign up to set email alerts
|

Layered rhyolite bands in a thick North Mountain Basalt flow: the products of silicate liquid immiscibility?

Abstract: The upper 35 m of a thick (~<175 m) Early Jurassic North Mountain Basalt flow at KcKay Head contains 25 cm thick differentiated layers that are separated by 130 cm sections of basalt. The lower layers are mafic, pegmatitic, and contain thin (2 cm), fine-grained 'rhyolite' bands. Evidence that the rhyolite represents a Si-rich immiscible liquid includes: (1) textures such as fiine-grained globules of Ferich pyroxene (once Fe-rich liquid) bordering pegmatite feldspar grains; (2) structureless, microcrystalline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…While silicic and mafic magmas are clearly miscible at temperatures above their liquidi [e.g., Kouchi and Sunagawa, 1985], the miscibility of such liquids at subliquidus temperatures is not well constrained. However, we note that plausible cases of immiscibility between mafic and silicic magmas have been observed both in the field [Philpotts, 1971[Philpotts, , 1972Bender et al, 1982;Greenough and Dostal, 1992] and in the laboratory under sub-liquidus conditions [Martin and Kushiro, 1991]. The observation of immiscibility is consistent with the enthalpy of mixing of basalt and dacitic melts being positive under hydrous conditions [Russell, 1990].…”
Section: Basic Methodssupporting
confidence: 76%
“…While silicic and mafic magmas are clearly miscible at temperatures above their liquidi [e.g., Kouchi and Sunagawa, 1985], the miscibility of such liquids at subliquidus temperatures is not well constrained. However, we note that plausible cases of immiscibility between mafic and silicic magmas have been observed both in the field [Philpotts, 1971[Philpotts, , 1972Bender et al, 1982;Greenough and Dostal, 1992] and in the laboratory under sub-liquidus conditions [Martin and Kushiro, 1991]. The observation of immiscibility is consistent with the enthalpy of mixing of basalt and dacitic melts being positive under hydrous conditions [Russell, 1990].…”
Section: Basic Methodssupporting
confidence: 76%
“…Similar textures have been recognized by other authors (e.g. Kontak et al, 2002) and immiscible thin fine-grained rhyolite bands have even been shown to have segregated from differentiated layers of lavas (Greenough and Dostal, 1992).…”
Section: Volcanic Provincessupporting
confidence: 86%
“…Many thick flood-basalt flows [1][2][3][4][5][6][7] and lava lakes [8][9][10][11] contain horizontal sheets of coarse-grained rock whose composition corresponds to liquid formed by approximately one-third fractional crystallization of the host basalt. Several mechanisms have been proposed for separating this liquid from the basalt, one of which involves expulsion of liquid from a crystal mush that undergoes compaction in the lower part of the flow 7 .…”
mentioning
confidence: 99%